Investigating the use of novel fluorescent nanosensors to measure chemical changes in bacterial surroundings - Perkins, Mark Edwin (2021)
The formation and persistence of microbial biofilms play an important role in infection and the biofouling of the environment. In order to eradicate these complex structures, further characterisation of the microniches that form within biofilms is vital. This study aimed to investigate whether fluorescent nanosensors could map pH and oxygen gradients in microbial biofilms.